Trophies of war and empire : the archival heritage of Ukraine, World War II, and the international politics of restitution - Patricia Kennedy Grimsted. (Ukrainian Research Institute, Harvard University, 2001)
Includes bibliographical references (pp. 581-693) and index (pp. 695-749).